Качество жизни Пермского края - Khomin A. V. (Осенний школьный марафон, 2015)
In this article, the author cites the changes in the population of the Perm region. It is noted that the Russian demographic program aims to change the unfavorable situation in the social sphere. A crucial role for the growth of reproductive activity, that is, an increase in population. Thus, the level of living conditions contributes to a strong family, increased motor activity of Russians, healthy lifestyle, systematic physical culture and sports.
Keywords: качество жизни; инновационные проблемы урбанизации; развитие физической культуры; развитие спорта; Quality of life; innovation problems of urbanization; development of physical culture and sports development